The intention of Muslim customers to adopt mobile banking: The case of Islamic banks in Indonesia - Heri Sudarsono; Muamar Nur Kholid; Aidha Trisanty; Maisaroh Maisaroh (Cogent Business & Management, 2022)
The purpose of this study is to examine the influence of innovation diffusion theory (IDT), perceived risk, customer awareness, and religiosity on customer intention in Islamic bank mobile banking (m-banking). This study examines 219 Islamic bank customers who accepted Islamic banking at various times. The PLS-SEM technique was used to evaluate data from 219 respondents with the assistance of Smart PLS 3.0. The data processing results show that compatibility, complexity, observability, awareness, and religiosity affect the intention to adopt mobile banking. Meanwhile, relative advantage, trialability, and perceived risk do not affect customers' intention to adopt m-banking. Religiosity has the greatest influence on customer intention in adopting m-banking compared to compatibility, observability, and awareness. As a result of these findings, Islamic banks must adhere to Islamic values when creating mobile banking technologies. Additionally, Islamic banks must continue to innovate to maintain a competitive advantage and mitigate risks associated with mobile banking.
Keywords: 650; religiosity; Islamic bank; perceived risk; awareness; innovation diffusion theory